Epidemiology of Cervix Uteri Cancer in Saudi Arabia from 2004 to 2017 - Alghamdi, Ibrahim (Indonesian Socety of Obstetrics and Gynecology, 2024)
Abstract: Objectives: This study investigates the epidemiological pattern of Cervix Uteri cancer (CUC) throughout all administrative regions of Saudi Arabia. It examines the frequency number and percentage of diagnosed cases, the age-specific incidence rate (AIR), the crude incidence rate (CIR), and the age-standardized incidence rate (ASIR) stratified by age group, year of diagnosis, and regions. Methods: A retrospective descriptive epidemiological investigation of all CUC cases documented in the Saudi Cancer Registry (SCR) between 2004 and 2017 was performed. Statistical Package for the Social Sciences, version 20.0, was utilized to analyse the data using descriptive statistics and the Kruskal-Wallis test (SPSS). Results: In total, 1,451 UCU diagnosed cases were reported to the SCR between January 2004 and December 2017. Northern, Eastern, and Tabuk regions had the highest ASIR of CUC among Saudi women (2.2, 2.0, and 2.0 per 100,000 women). In contrast, among Saudi women, Jazan had the lowest overall ASIR of CUC (0.7 per 100,000 women, respectively). Conclusion: The ASIRs of CUC in Saudi Arabia decreased slightly from 2004 to 2017. The Northern, Eastern, and Tabuk regions of Saudi Arabia had the highest ASIR of CUC among Saudi women, while women in Jazan, Saudi Arabia, were proven to be the least affected by CUC. Keywords: Cancer epidemiology; Cervix Uteri cancer; Saudi Cancer Registry; oncology; Incidence rate.